Caregiving in multiple sclerosis and quality of life: A meta-synthesis of qualitative research. Issue 6 (2nd June 2016) - Topcu, Gogem; Buchanan, Heather; Aubeeluck, Aimee; Garip, Gülcan
Abstract : Objective: The lack of adequate conceptualisation and operationalisation of quality of life (QoL) limits the ability to have a consistent body of evidence to improve QoL research and practice in informal caregiving for people with multiple sclerosis (MS). Thus, we conducted a meta-synthesis of qualitative research to improve the conceptual understanding of the experiences of MS carers and to identify factors that affect carers' QoL. Design: Systematic searches of five electronic databases yielded 17 qualitative studies which were synthesised using the principles of meta-ethnography. Results: The synthesis resulted in nine inter-linking themes: Changes and losses; challenges revolving around MS; caregiving demands; burden of care; future concerns; external stressors; experiences of support; strategies used in managing the caregiving role; and motivating factors. Our findings suggest that MS carers can have both positive and negative experiences which may bring challenges and rewards to the carers. Conclusion: We present a proposed QoL model for MS caregiving which can be used to inform the development of interventions for MS carers to improve their QoL. However, further empirical research is needed to examine the utility of this model and to explore the concept of QoL in MS carers in more detail.